Effectiveness of Learning Methods in Accounting Study Programs: Comparison in Learning Results through Advanced Methods, Case Study, and Simulation - Indra Komara; Prima Yusi Sari (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
This study aims to examine which learning method is the most effective among the face-to-face learning methods, case studies, and simulations of learning outcomes (learning outcomes) in the form of learning outcomes of problem solving abilities, interpersonal skills, and self-awareness. The independent variable in this research is face to face learning method, case study learning method, and simulation learning method. The dependent variable in this study is the ability to solve problems, interpersonal skills and self awareness. The respondents in this study were students of the Accounting study program at the Faculty of Economics and Business, Padjadjaran University. The number of samples in this study were 135 students, 65 people consisted of 2015 and 70 people of 2016. The sampling technique used was simple random sampling using the Slovin formula. This study uses multiple linear regression statistical analysis to determine the effect of independent variables on the dependent variable. The level of significance used in this study was 5%. The results showed that partially face-to-face learning methods had a significant positive effect on problem solving skills, interpersonal skills, and self-awareness of students. Partially the case study learning method has a significant positive effect on problem solving abilities and interpersonal skills, while self-awareness has no significant effect. Partially the simulation learning method has a significant positive effect on problem solving skills, interpersonal skills, and self-awareness of students. Simultaneously face to face learning methods, case study learning methods, and simulation learning methods have a significant positive effect on problem solving skills, interpersonal skills, and self-awareness of students.